Testing the relationship between inhibitory control and soda consumption: An event-related potential (ERP) study. (1st June 2022) - Eberly, Hänel W.; Carbine, Kaylie A.; LeCheminant, James D.; Larson, Michael J.
Abstract: The intake of sugar-sweetened beverages (SSB) may detrimentally influence health outcomes. Drinking less soda may help manage SSB consumption, as soft drinks are a top contributor to SSB intake. One cognitive factor that may influence soda consumption is inhibitory control, or the ability to withhold a dominant response in order to correctly respond to one's environment. Increased inhibitory control plays a role in decreasing consumption of high-calorie foods and strengthening inhibitory control may help individuals manage their food intake. However, neural response to soda beverages versus traditional non-sweetened beverages, such as water, and how it relates to soda consumption is unknown. In a sample of 116 healthy individuals ( M = 20.56; SD = 2.08; 47.4% female), we measured soda consumption and tested event-related potential (ERP) measures of inhibitory control, including the N2 and P3 components, during soda-specific and neutral comparison go/no-go tasks. Female participants consumed less soda on average than males, and as participants got older, they consumed less soda. Participants showed faster response times and higher accuracy on the soda-specific go/no-go task compared to the neutral go/no-go task. ERP results indicated inhibitory control was greater when individuals withheld dominant responses to soda stimuli rather than neutral stimuli. Neither N2 no-go amplitude on the soda-specific go/no-go task nor P3 no-go amplitude on the soda-specific task predicted measures of soda intake. Results suggest greater inhibitory control resources are required when withholding responses to soda beverages compared to neutral stimuli, but inhibitory control ERPs did not predict day-to-day soda intake. Highlights: Tested the relationship between soda consumption and measures of soda inhibition. Females consumed less soda than males. Accuracy and response times were improved to soda-specific inhibition than neutral. Event-related potential (ERP) measures of inhibition were stronger to soda than neutral. Soda inhibition measures did not predict self-reported soda consumption.